The Impact of Maternal Depression on Children’s Behaviour - Wan Nur Amirah binti Aminuddin; Amaluddin bin Ahmad (Asian Journal of Medicine & Health Sciences, 2023)
Introduction: Maternal depression has become a growing health issue due to its adverse impact on both mother and child. About 1 in every 10 children are being taken care by depressed mothers. The diverse and serious implications of maternal depression on children including cognitive, emotional, behavioural, home safety, health practices, and social adaptation have been elucidated in published literature. However, this study solely focused to address the effect of maternal depression on a child’s behavioural domain. Objective: To conduct a literature review and determine the impact of maternal depression on children’s behaviour. Methodology: A literature review was conducted on the published studies regarding maternal depression from 1991 to 2021 and the selection criteria were based on the study objectives. Electronic databases such as PubMed, Science Direct, Up to date, Scopus, and Google Scholar were used to obtain studies on the association of maternal depression and a child’s behavioural problems. Results: Studies have documented that maternal depression was significantly associated with internalizing and externalizing behavioural problems in children. In terms of the timing, earlier exposure to maternal depression such as postnatal depression leads to the development of internalizing behavioural problems; while externalizing problems were mostly associated with concurrent maternal depressive symptoms. Persistent depression increases the risk of developing behavioural problems, and significant severe clinical maternal depressive symptoms were prevalent among a greater proportion of children developing behavioural problems. Conclusion: Findings have shown a notable association between maternal depression and child’s behavioural domain. The internalizing and externalizing behavioural problems will not only cause a troubled childhood but will also develop future issues in adolescence and adulthood. Thus, knowledge of these associations would facilitate clinicians to administer early intervention and prevention strategies to mitigate the devastating impact of this serious public health concern.